L-carnitine ameliorates the muscle wasting of cancer cachexia through the AKT/FOXO3a/MaFbx axis - Wu, Changpeng; Zhu, Mingxing; Lu, Zongliang; Zhang, Yaowen; Li, Long; Li, Na; Yin, Liangyu; Wang, He; Song, Wei; Xu, Hongxia (Nutrition & metabolism, 2021)
Recent studies suggest potential benefits of applying L-carnitine in the treatment of cancer cachexia, but the precise mechanisms underlying these benefits remain unknown. This study was conducted to determine the mechanism by which L-carnitine reduces cancer cachexia. C2C12 cells were differentiated into myotubes by growing them in DMEM for 24 h (hrs) and then changing the media to DMEM supplemented with 2% horse serum. Differentiated myotubes were treated for 2 h with TNF-[alpha] to establish a muscle atrophy cell model. After treated with L-carnitine, protein expression of MuRF1, MaFbx, FOXO3, p-FOXO3a, Akt, p-Akt, p70S6K and p-p70S6K was determined by Western blotting. Then siRNA-Akt was used to determine that L-carnitine ameliorated cancer cachexia via the Akt/FOXO3/MaFbx. In vivo, the cancer cachexia model was established by subcutaneously transplanting CT26 cells into the left flanks of the BALB/c nude mice. After treated with L-carnitine, serum levels of IL-1, IL-6 and TNF-[alpha], and the skeletal muscle content of MuRF1, MaFbx, FOXO3, p-FOXO3a, Akt, p-Akt, p70S6K and p-p70S6K were measured. L-carnitine increased the gastrocnemius muscle (GM) weight in the CT26-bearing cachexia mouse model and the cross-sectional fiber area of the GM and myotube diameters of C2C12 cells treated with TNF-[alpha]. Additionally, L-carnitine reduced the protein expression of MuRF1, MaFbx and FOXO3a, and increased the p-FOXO3a level in vivo and in vitro. Inhibition of Akt, upstream of FOXO3a, reversed the effects of L-carnitine on the FOXO3a/MaFbx pathway and myotube diameters, without affecting FOXO3a/MuRF-1. In addition to regulating the ubiquitination of muscle proteins, L-carnitine also increased the levels of p-p70S6K and p70S6K, which are involved in protein synthesis. Akt inhibition did not reverse the effects of L-carnitine on p70S6K and p-p70S6K. Hence, L-carnitine ameliorated cancer cachexia via the Akt/FOXO3/MaFbx and p70S6K pathways. Moreover, L-carnitine reduced the serum levels of IL-1 and IL-6, factors known to induce cancer cachexia. However, there were minimal effects on TNF-[alpha], another inducer of cachexia, in the in vivo model. These results revealed a novel mechanism by which L-carnitine protects muscle cells and reduces inflammation related to cancer cachexia.